Strategic theory for the 21st century - Yarger, Harry R. (Carlisle Barracks Strategic Studies Institute, 2006)
The word "strategy" pervades American conversation and our news media. We tend to use strategy as a general term for a plan, a concept, a course of action, or a "vision" of the direction in which to proceed at the personal, organizational, and governmental-local, state, or federal-levels. Such casual use of the term to describe nothing more than "what we would like to do next" is inappropriate and belies the complexity of true strategy and strategic thinking. It reduces strategy to just a good idea without the necessary underlying thought or development. It also leads to confusion between strategy and planning, confining strategic possibilities to near-time planning assumptions and details, while limiting the flexibility of strategic thought and setting inappropriately specific expectations of outcomes. This "little book"-actually a monograph-talks about big strategy, strategy at the highest levels of the nation-state. It is applicable to grand strategy, national security strategy, national military. . .
"February 2006."
Keywords: Strategy